PERBANDINGAN HUKUM PERKAWINAN SUDAN DAN HUKUM PERKAWINAN INDONESIA - Sarina Aini; Maisyarah Rahmi Hasan (SYARIAH: Journal of Islamic Law, 2023)
Sudan is a power that enforces Islamic Law as a statutory principle of unity. Sudan also a country consisting of various ethnicities and religions. Likewise, Indonesia consists of various tribes, cultures and nations and their religious diversity. Sudan and Indonesia are countries that have renewed Islamic law In the field of marriage, both Sudan and Indonesia have their own legal stipulations in this field. In this study, the author will describe the differences between Sudanese marriage law and Indonesian marriage law.